Peran United States Agency for International Development (USAID) terhadap Kudeta Militer Myanmar - Amanda Khairunissa Yunus; Nindya Raihan Zani; Rihhadatul Aisya; Reza Santika; Sonia Pesliko (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2023)
Myanmar has experienced a democracy crisis and is facing a violent war for human rights by the military junta. The conflict between the military and the victory of Aung San Suu Kyi's party, namely the NLD (National League for Democracy) party, caused Myanmar to experience a coup since February 2021. The human rights urgency of the Myanmar problem caused international institutions and a number of countries such as the United States to help Myanmar in resolving the problem by both providing financial assistance and other government development assistance to Myanmar, through its agency USAID (United States Agency for International Development). The existence of USAID assistance to Myanmar indicates that there are things that encourage US assistance to Myanmar which raises questions; what are the interests of the US through USAID in helping Myanmar. Which questions will be answered in this paper with a historical approach based on the theory of liberalism. Keywords: Military Coup; liberalism; Myanmar; USAID References Aida, R. N. (2021, February 12). Kudeta Myanmar, Sebab, dan Apa yang Sebenarnya Terjadi? KOMPAS.Com. https://www.kompas.com/tren/read/2021/02/12/123000265/kudeta-myanmar sebab-dan-apa-yang-sebenarnya-terjadi-?page=1 Bakry, U.S. (2017). Dasar-Dasar Hubungan Internasional. Jakarta: Kencana Devi, K. S. (2014). Myanmar under the military rule 1962-1988. International Research Journal of Social Sciences, 3(10), 46-50. http://www.isca.in/IJSS/Archive/v3/i10/8.ISCA-IRJSS-2014-173.pdf Enos, O (2021). Scaling up the U.S. Response to the Coup in Burm (Report No. 3629). The Heritage Foundation. https://www.heritage.org/asia/report/scaling-the-us-response-the-coup-Myanmar Hidriyah, S. (2011). Proses Demokratisasi Myanmar Menuju Pemilu Presiden Tahun 2012. P3DI Sekretariat Jenderal DPR RI, Vol. III, No. 24 (December 2011):1-8. http://berkas.dpr.go.id/puslit/files/info_singkat/Info%20Singkat-III-24-II-P3DI-Desember-2011- 60.pdf. History | Myanmar | U.S. Agency for International Development. (n.d.). U.S. Agency for International Development. Retrieved August 6, 2021, from https://www.usaid.gov/Myanmar/history Institute of Southeast Asian Studies. (2010). Timeline: US-Myanmar/Myanmar Relations. Timeline: US Myanmar/Myanmar Relations, 32(3), 434–436. https://www.jstor.org/stable/25798870 International Crisis Group (2021). Responding to the Myanmar Coup. https://d2071andvip0wj.cloudfront.net/b166-responding-to-the-myanmar-coup.pdf . Jakarta, E. U. S. (2019, August 8). Lembar Fakta: Amerika Serikat dan ASEAN – Kemitraan Abadi. Kedutaan Besar dan Konsulat AS di Indonesia. https://id.usembassy.gov/id/lembar-fakta amerika-serikat-dan-asean-kemitraan-abadi/ . O.P.R. (2001, February 11). USAID Immediately Redirects 42 Million in Response to the Military. U.S. Agency for International Development. https://www.usaid.gov/news-information/press releases/feb-11-2021-usaid-immediately-redirects-42-million-response-military-coup-Myanmar O.P.R. (2021, May 18). United States Announces Nearly 155 Million in New Funding for the. U.S. Agency for International Development. https://www.usaid.gov/news-information/press releases/may-18-2021-us-announces-nearly-155-million-new-funding-Myanmar-bangladesh crisis Tarnoff, C. (2018). The Marshall plan: Design, accomplishments, and significance (Vol. 18). Congressional Research Service. https://www.ethiopianregistrar.com/files/sgp/crs/row/r45079.pdf . Toosi, N. (2018, July 31). Trump officials split over punishing Myanmar for atrocities. POLITICO. https://www.politico.com/story/2018/07/31/myanmar-rohingya-white-house-trump-officials 752730 U.S. Agency for International Development. (2021, July). U.S. Foreign Aid by Country|Myanmar. Foreign Aid Explorer. https://foreignassistance.gov/cd/MMR?implementing_agency_id=1&measure=Obligations&fisca l_year=2017 U.S. Agency for International Development. (2021a, June). U.S. Foreign Aid by Country|Myanmar. Foreign Aid Explorer. https://foreignassistance.gov/cd/MMR?fiscal_year=2020&implementing_agency_id=1&measure =Obligations U.S. Relations With Myanmar. (2021, June 3). United States Department of State. https://www.state.gov/u-s-relations-with-Myanmar/ Viotti, P. R dan Mark V. K. (2012).